Pediatric Sequential Organ Failure Assessment Score: Modifikasi Sistem Skor Pada Sepsis Anak - Rismala Dewi (PENGURUS BESAR IKATAN DOKTER INDONESIA (PB IDI), 2020)
Introduction: Society of Critical Care Medicine (SCCM) and European Society of Intensive Care Medicine (ESICM) defined sepsis as life-threatening organ dysfunction caused by dysregulated host response to infection. Sequential Organ Failure Assessment (SOFA) was chosen and validated as a scoring system to predict organ dysfunction in adult patients with infection because SOFA score showed an equal or even better result than another scoring system in predicting hospital mortality. To adapt sepsis-3 definition in pediatric patients, SOFA was modified according to age into pediatric sequential organ failure assessment (pSOFA) score. The result showed that pSOFA score on admission day, day 2, 4, 7 and 14 in Pediatric Intensive Care Unit (PICU) was better in predicting prognosis for pediatric oncology patients on mechanical ventilator, pediatric patients with sepsis and better in predicting 30-days mortality than another scoring system. However, pSOFA failed to predict the length of stay pediatric patients in PICU.